140k views
0 votes
Find the vectors, not with determinants, but by using properties of cross products.

(i + j) × (i - j)

and

k × (i - 2j)

User TimP
by
6.8k points

1 Answer

5 votes

(\mathbf i+\mathbf j)*(\mathbf i-\mathbf j)=(\mathbf i+\mathbf j)*\mathbf i+(\mathbf i+\mathbf j)*(-\mathbf j)

since the cross product is distributive over addition. By anticommutativity,


(\mathbf i+\mathbf j)*\mathbf i+(\mathbf i+\mathbf j)*(-\mathbf j)=-(\mathbf i*(\mathbf i+\mathbf j))-(-\mathbf j)*(\mathbf i+\mathbf j))

Scalars can be factored, so


-(\mathbf i*(\mathbf i+\mathbf j))-(-\mathbf j)*(\mathbf i+\mathbf j))=-(\mathbf i*(\mathbf i+\mathbf j))+\mathbf j*(\mathbf i+\mathbf j))

Using the distributive property again,


-(\mathbf i*(\mathbf i+\mathbf j))+\mathbf j*(\mathbf i+\mathbf j))=-(\mathbf i*\mathbf i+\mathbf i*\mathbf j)+\mathbf j*\mathbf i+\mathbf j*\mathbf j

Any vector crossed with itself is the zero vector, so you get


-(\mathbf i*\mathbf i+\mathbf i*\mathbf j)+\mathbf j*\mathbf i+\mathbf j*\mathbf j=-(\mathbf i*\mathbf j)+\mathbf j*\mathbf i

Because
\mathbf i*\mathbf j=\mathbf k, and by anticommutativity, you are left with


-(\mathbf i*\mathbf j)+\mathbf j*\mathbf i=-\mathbf k-(\mathbf i*\mathbf j)=-\mathbf k-\mathbf k=-2\mathbf k

Next, without outlining which properties are being used,


\mathbf k*(\mathbf i-2\mathbf j)=\mathbf k*\mathbf i+2(\mathbf j*\mathbf k)=2\mathbf i+\mathbf j
User Noah Freitas
by
6.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.